INDICATION OF HPV VACCINE IN THE TREATMENT OF A CHILD WITH RECURRENT LARYNGEAL PAPILLOMATOSIS: A CASE STUDY - Letícia Ferreira, Bruna; Maurícia Souza, Luanna; Aparecida Alves Barbosa, Romana; Cristina Teixeira, Claudia; de Freitas Villela, Matheus; Coutinho Ferreira, Cinara; Kelly Duarte de Oliveira Lopes, Greicy; Rocha de Oliveira, Bryan; Felipe Antunes da Silva, Leandro; Gabrielle Rodrigues Peixoto, Sarah; Emanuelle Rocha dos Santos, Hanna; Gonçalves Silva Pereira, Sabrina; et al. (Health and Society, 2024)
Laryngeal papillomatosis or Recurrent Respiratory Papillomatosis (PRR) is the main cause of benign laryngeal neoplasia characterized by the proliferation of epithelial lesions with the presence of warts, called papillomas. These are often multiple and recurrent, being caused by The Human Papilloma Virus (HPV). Currently, there are no surgical or curative medical treatments for the disease. The literature indicates several options, including the quadrivalent HPV vaccine. In this sense, this study sought to report a clinical case of a child with recurrent respiratory papillomatosis, with emphasis on the quadrivalent HPV vaccine used as adjuvant therapy. In this case study, it was evidenced that immunization can be used as adjuvant therapy.